2022
DOI: 10.1186/s12889-022-14456-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of hypertension among urban slum dwellers in Bangladesh

Abstract: Background In low- and middle- income countries such as Bangladesh, urban slum dwellers are particualry vulnerable to hypertension due to inadequate facilities for screening and management, as well as inadequate health literacy among them. However, there is scarcity of evidence on hypertension among the urban slum dwellers in Bangladesh. The present study aimed to determine the prevalence and factors associated with hypertension among urban slum dwellers in Bangladesh. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
2
2
1
Order By: Relevance
“…However, the overall prevalence is much lower compared to the burden among older adult and elderly population estimates from nationally representative survey data from India (LASI) (36%) [ 17 ]. The burden of hypertension in the present study was also nearly similar to that observed in populated aged ≥ 35 years from urban slum areas in Bangladesh (28.3%) [ 29 ], higher compared to urban slums in Brazil (12.3%) [ 28 ] but lower than urban slums in Kolkata (42%) [ 30 ]. Our study found the prevalence of hypertension to be higher in males (32.21%) than females (26.25%).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, the overall prevalence is much lower compared to the burden among older adult and elderly population estimates from nationally representative survey data from India (LASI) (36%) [ 17 ]. The burden of hypertension in the present study was also nearly similar to that observed in populated aged ≥ 35 years from urban slum areas in Bangladesh (28.3%) [ 29 ], higher compared to urban slums in Brazil (12.3%) [ 28 ] but lower than urban slums in Kolkata (42%) [ 30 ]. Our study found the prevalence of hypertension to be higher in males (32.21%) than females (26.25%).…”
Section: Discussionsupporting
confidence: 85%
“…Current tobacco users in previously diagnosed hypertension cases in this study was 113 (11.66%), a finding lower than that observed in cross-sectional studies from slums in Bangladesh (27.33%) [ 29 ], Kolkata (44.35%) [ 30 ], Kenya (32.3%) [ 47 ] and Egypt (43.65%) [ 48 ]. Among those who smoked tobacco, 41.6% women and 35.51% men were hypertensive in our study, comparatively higher than the findings from NFHS-4 (2015–2016), where 15.3% women and 22.4% men who smoked tobacco were found hypertensive [ 49 ].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The consistent findings were evident in studies conducted in Bangladesh, India, China and Peru. 21,24,[26][27][28] Our study observed that unemployed or retired persons were more likely to have diabetes than currently working individuals. Moreover, the odds of developing diabetes was significantly higher among the person with higher educational level than those without formal schooling.…”
Section: Discussionmentioning
confidence: 53%